2021
DOI: 10.1038/s41598-021-82008-7
|View full text |Cite
|
Sign up to set email alerts
|

Delta/Theta band EEG activity shapes the rhythmic perceptual sampling of auditory scenes

Abstract: Many studies speak in favor of a rhythmic mode of listening, by which the encoding of acoustic information is structured by rhythmic neural processes at the time scale of about 1 to 4 Hz. Indeed, psychophysical data suggest that humans sample acoustic information in extended soundscapes not uniformly, but weigh the evidence at different moments for their perceptual decision at the time scale of about 2 Hz. We here test the critical prediction that such rhythmic perceptual sampling is directly related to the st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 86 publications
2
9
0
Order By: Relevance
“…This phenomenon was not only present between the to-be-attended and to-be-ignored ear but also in the same ear between both attention conditions. These results are very similar to that observed in the visual and recently emerging auditory rhythmic sampling literature for both neural activity and behavioral performance, expanding it to the level of the auditory receptor (Fiebelkorn et al, 2013; Ho et al, 2017; Kayser, 2019; Kubetschek & Kayser, 2021; Landau & Fries, 2012; Plöchl et al, 2021; Spyropoulos et al, 2018). Moreover, on the basis of the PLV analysis it seems very unlikely that these effects are driven by eye movement-related activity.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This phenomenon was not only present between the to-be-attended and to-be-ignored ear but also in the same ear between both attention conditions. These results are very similar to that observed in the visual and recently emerging auditory rhythmic sampling literature for both neural activity and behavioral performance, expanding it to the level of the auditory receptor (Fiebelkorn et al, 2013; Ho et al, 2017; Kayser, 2019; Kubetschek & Kayser, 2021; Landau & Fries, 2012; Plöchl et al, 2021; Spyropoulos et al, 2018). Moreover, on the basis of the PLV analysis it seems very unlikely that these effects are driven by eye movement-related activity.…”
Section: Discussionsupporting
confidence: 86%
“…for simple target detection (Ng et al, 2012); speech perception (Poeppel & Assaneo, 2020); auditory scene exploration (Kayser, 2019)). Albeit early studies failed to provide evidence for the existence of thetarhythmic oscillations in auditory attention (İlhan & VanRullen, 2012;Zoefel & Heil, 2013), numerous recent findings from both cortical and behavioral data speak for their existence (Ho et al, 2017(Ho et al, , 2019Kayser, 2019;Kubetschek & Kayser, 2021;Ng et al, 2012;Plöchl et al, 2021). Interestingly, in bilateral pitch-identification tasks behavioral performance theta-rhythmically oscillates in antiphase between the two ears (Ho et al, 2017;Plöchl et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Ponjavic-Conte et al (2012) reported lower activity in the θ band during auditory attention distraction, but they only inspected the Cz electrode. The low frequencies activity have also been implicated on numerous occasions in auditory perceptual sampling processes (Kubetschek and Kayser, 2021). Finally, we observe both at Cz and Pz electrodes, like at the left grid of the cEEGrid, increased β and θ power spectral variations for misses compared to hits.…”
Section: Discussionsupporting
confidence: 62%
“…Previously, we also found that alpha power was highly activated in bilateral temporal areas after specific sound stimuli that were statistically different in terms of the type of sound [ 48 ]. In addition, the delta and theta bands are known to be associated with shaping the segmentation and perceptual influence of acoustic information [ 93 ]. Although this study is based on animal experimental data, similar speech-related components, as compared to the previous studies on human subjects, were observed in the TFR analyses.…”
Section: Discussionmentioning
confidence: 99%